HUBUNGAN ANTARA PERCEIVED ORGANIZATIONAL SUPPORT DENGAN WORK ENGAGEMENT PADA GURU HONORER SEKOLAH DASAR - Masithoh Chairun Nisa, Vidalisia; Noviya Andriyani, Isnanita (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Work engagement does not occur automatically so that honorary teachers in an organization cannot be separated from organizational support. The purpose of this study is to see and explain the relationship between perceived organizational support and work engagement in honorary elementary school teachers in Kulon Progo. This research uses quantitative methods with a correlational study approach. Data were collected using purposive sampling technique, involving 87 honorary teachers from 651 elementary school honorary teachers in Kulon Progo. The measurement instruments used were the “Perceived Organizational Support” scale (? = 0.89) and the “Work Engagement” scale (? = 0.86). The results of hypothesis testing analysis using the Pearson correlation method showed a significant and positive relationship between perceived organizational support and work engagement. The significance value of 0.021 (p < 0.05) indicates that the relationship is significant. Pearson correlation of 0.248 indicates a positive relationship, which means that an increase in the level of perceived organizational support will be followed by an increase in the level of work engagement. Vice versa, a decrease in the level of perceived organizational support directly decreases the level of work engagement. ABSTRAK Work engagement tidak terjadi secara otomatis sehingga guru honorer dalam suatu organisasi tidak terlepas dari organizational support. Tujuan penelitian ini adalah untuk melihat dan menjelaskan hubungan antara perceived organizational support dengan work engagement pada guru honorer sekolah dasar di Kulon Progo. Penelitian ini menggunakan metode kuantitatif dengan pendekatan correlational study. Pengambilan data menggunakan teknik purposive sampling, melibatkan 87 guru honorer dari 651 guru honorer sekolah dasar di Kulon Progo. Instrumen pengukuran yang digunakan adalah skala “Perceived Organizational Support” (? = 0,89) dan skala “Work Engagement” (? = 0,86). Hasil analisis uji hipotesis menggunakan metode korelasi Pearson menunjukkan adanya hubungan signifikan dan positif antara perceived organizational support dan work engagement. Nilai signifikansi sebesar 0,021 (p < 0,05) menunjukkan bahwa hubungan tersebut signifikan. Pearson correlation sebesar 0,248 mengindikasikan hubungan positif, yang berarti kenaikan tingkat perceived organizational support akan diikuti oleh kenaikan tingkat work engagement. Begitu pula sebaliknya, menurunnya tingkat perceived organizational support secara langsung menurunkan tingkat work engagement.